Method for Determining ε-Aminocaproic Acid (EACA) in Blood Plasma, Based on the Antifibrinolytic Properties of this Compound - Wolosowicz, Nina; Niewiarowski, Stefan; Czerepko, Kazimierz (Thrombosis and Haemostasis, 1963)
A method was elaborated for determining e-aminocaproic acid (EACA) in blood plasma, based upon this compound’s antifibrinolytic activity.Oxalated plasma was deproteinized in a boiling water-bath using trichloracetic acid. The latter was removed from plasma filtrate by means of ether extraction and the effect of the deproteinized extract on clot fibrinolysis time under standard conditions was tested. There was found a linear correlation of the logarithm of clot lysis time with EACA concentration.The method appears to be fast and reliable, making possible serial determinations of the EACA level in blood plasma, the error being within the limits of 3 percent. It is suitable for the EACA level in plasma exceeding 2 mgVo.The method is most specific. Various amino acids appearing naturally (except cysteine) do not interfere with determinations.The EACA metabolism in vivo may be successfully studied using the above method.